Thrombin Induces Surface and Intracellular Secretion of Amyloid Precursor Protein from Human Endothelial Cells - Ciallella, John R.; Figueiredo, Helmer; Smith-Swintosky, Virginia; McGillis, Joseph P. (Thrombosis and Haemostasis, 1999)
Thrombin, a major coagulant and inflammatory mediator, was shown to regulate amyloid precursor protein (APP) secretion. APP is the protein from which the amyloid beta peptide (Aß) is derived. Aß forms the core of vascular and cerebral plaques in Alzheimer’s disease (AD). In this study, human umbilical vein endothelial cells (HUVEC) were used to examine the effects of thrombin on APP expression. Cell supernatants from thrombin-treated HUVEC were immunoblotted to measure secreted APP. Thrombin-induced secretion of APP peaks at approximately 30 min post-treatment. Immunohistochemical analysis found that APP is not colocalized with or secreted through the same pathway as coagulation factor VIII. The secretion of APP is thrombin receptor-mediated, since it is inhibited by the thrombin antagonist N-Acetyl-D-Phe-Pro1Amido-4-Guanidino-Butyl-1-Boronic Acid. It also is induced by treatment with a calcium ionophore. Moreover, APP secretion is protein kinase C (PKC)-dependent because it is blocked by the PKC inhibitor bisindolylmaleimide. APP secretion also occurs from the cell surface, possibly through direct cleavage by thrombin. Immunoreactivity on the surface of HUVEC decreased after thrombin treatment but not after treatment with a non-proteolytic thrombin receptor activator. These data suggest that thrombin induces APP secretion through a PKC-dependent mechanism, as well as from the cell surface. Our results are consistent with thrombin playing a role in AD pathology.